Authentic leadership and employee engagement in a South African organisation. - Abdul Kader, Junaid (My University, 2017)
Employee engagement has received attention from business and academic sectors, but is not completely understood. Likewise, leadership has received attention which has led to authentic leadership being a recent model of leadership. Organisations may benefit, particularly now in the midst of an economic downturn, by understanding the relationship between authentic leadership and employee engagement. Hopefully, this understanding will improve leadership behaviour aimed at increasing employee engagement. The authentic leadership model by Walumbwa, Avolio, Gardner, Wernsing, and Peterson (2008) and the employee engagement by Kahn (1990) were used to explore the relationship between authentic leadership and employee engagement in a South African organisation. The relationship was explored by a literature review to understand the theoretical link and then through surveys to collect data. Co-inertia mapping was then used to quantify and validate the relationship. Three major associations between authentic leadership and employee engagement were found. The three major associations were named; Appropriateness, Consistent Involvement and Open Book. Leaders who want to influence employee engagement should focus on relationships, treat employees in the appropriate fashion, be consistently involved, and foster trust by being ethical.
MBA Thesis
Keywords: Employee motivation -- South Africa,Management -- Employee participation -- South Africa,Leadership -- South Africa